Effect of microelement and chemical fungicides on biocontrol effect of Trichoderma T23 - ZHUANG Jing-hua; GAO Zeng-gui; YANG Chang-cheng; LIU Xian; CHEN Jie (浙江大学学报. 农业与生命科学版)
Recently there have been many reports about soil diseases controlled by Trichoderma, but few could be applied on agriculture production in large areas. T23 isolated from soil around plant roots in the field by Biopesticide Engineering Center of Shenyang Agricultural University could control effectively Cucurbits Fusarium Wilt. The effects of 9 microelements which include copper, zinc, iron, boron, molybdenum, calcium, manganese, magnesium, potassium and frequently-used chemical fungicides, such as-carbendazim, thiram, thiophanate-methyl, chlorothalonil and hymexazol on the growth and the amounts of spores of Fusarium oxysporum FJ and Trichoderma T23 were studied. The effects of those factors on control effect of T23 to melon diseases were discussed and gave basis for the screening of synergistic agents and fungicides in controlling synergistically the pathogen.The results showed that copper sulfate, zinc sulfate, ferric sulfate and boric acid at concentration of 10-1000 μg/mL had the stronger inhibition to F. oxysporum, while weaker inhibition to Trichoderma. Ammonium molybdate, ferrous sulfate, calcium sulfate and potassium dihydrogen phosphate were the ideal the synergistic agent for accelerating the growth and sporulation of Trichoderma, and germination of melon seeds and growth of melon radicle. Melon Fusarium wilt was controlled by Trichoderma combined with ammonium molybdate and calcium sulfate. The relative control effect reached to 73.95%-71.36%.Several fungicides used generally in soil had a different effect on the growth of F. oxysporum and Trichoderma. Carbendazim appeared a strong inhibition to the growth of two strains, with EC50 of 3.01 mg/L and 0.75 mg/L, respectively. Trichoderma had the strong resistance to thiram which control to Fusarium oxysporum was not ideal in field. Hymexazol which EC50 was 261 mg/L and Trichoderma had the synergistical effect on controlling to F. oxysporum. Trichoderma could reproduce in soil treated with hymexazol at ratio of 2000-4000. Relative control effect of hymexazol combined with Trichoderma to oxysporum reached to 79.26%, which was higher by 15.19% and 38.75% than the solo controlling effect respectively.